Discordance of Low-Density Lipoprotein Cholestrol and Non-High-Density Lipoprotein Cholestrol and Coronary Artery Disease Severity - Kurmus,Ozge (2020)
Abstract Background: A sizeable proportion of patients have discordant low-density lipoprotein cholesterol (LDL-C) and non-high-density lipoprotein cholesterol (non-HDL-C). Objectives: We assessed the relationship between discordance of LDL-C and non-HDL-C and coronary artery disease (CAD) severity. Methods: We retrospectively evaluated the data of 574 consecutive patients who underwent coronary angiography. Fasting serum lipid profiles were recorded, SYNTAX and Gensini scores were calculated to establish CAD complexity and severity. We determined the medians for LDL-C and non-HDL-C to examine the discordance between LDL-C and non-HDL-C. Discordance was defined as LDL-C greater than or equal to the median and non-HDL-C less than median; or LDL-C less than median and non-HDL-C greater than or equal to median. A p value < 0.05 was accepted as statistically significant. Results: LDL-C levels were strongly and positively correlated with non-HDL-C levels (r = 0.865, p < 0.001) but 15% of patients had discordance between LDL-C and non-HDL-C. The percentage of patients with a Gensini score of zero or SYNTAX score of zero did not differ between discordant or concordant groups (p = 0.837, p = 0.821, respectively). Mean Gensini and SYNTAX scores, percentage of patients with Gensini score ≥20 and SYNTAX score >22 were not different from group to group (p = 0.635, p = 0.733, p = 0.799, p = 0.891, respectively). Also, there was no statistically significant correlation between LDL-C and Gensini or SYNTAX scores in any of the discordant or concordant groups. Additionally, no correlation was found between non-HDL-C and Gensini or SYNTAX score. Conclusions: While there was discordance between LDL-C and non-HDL-C (15% of patients), there is no difference regarding CAD severity and complexity between discordant and concordant groups.